AKTIVITAS ANTIBAKTERI EKSTRAK DAUN TENGGULUN (Protium javanicum Burm. F.) TERHADAP BAKTERI Staphylococcus aureus - Puspawati, N. M.; Widiari, N. L. P. F.; Sukadana, I M. (Jurnal Kimia (Journal of Chemistry); Vol.14 No.1 Januari 2020DO - 10.24843/JCHEM.2020.v14.i01.p10, 2020)
This study aims to examine the antibacterial activity of n-hexane, ethyl acetate, and n-butanol extract of tenggulun leaves ( Protium javanicum Burm. F.) in inhibiting the growth of S. aureus bacteria and determine the minimum inhibitory concentration of the most active extracts and identify its active compounds. A total of 1000 g of tenggulun leaf powder was macerated with methanol and 91.78 g of crude methanol extract was obtained which was further partitioned into n-hexane, ethyl acetate, and n-butanol extracts. Antibacterial activity test was carried out using the diffusion well method and the result showed that the ethyl acetate extract at a concentration of 20% was strongly able to inhibit the growth of S. aureus bacteria with inhibition zones of 20.08 mm, followed by n-butanol 16.66 mm, and n-hexane 13.33 mm. The minimum concentration of ethyl acetate extract was 0.2% in inhibiting the growth of S. aureus with inhibition zone diameter of 6.20 mm. Separation of the active ethyl acetate extract was conducted by silica gel column chromatography with mobile phase of n-hexane: ethyl acetate (7.5: 2.5) gave 6 combined fractions. Fractions B, G, H and I showed antibacterial activity at concentrations of 50% with a diameter of inhibition zone of 5.62 mm, 6.87 mm, 8.50 mm, and 6.75 mm respectively. The results of mass spectra analysis from the chromatogram peaks of LC-MS / MS suggested that the G and I fractions were tentatively identified as crotarin, benzophenone-2, and medroxyprogesterone acetate which may contributed to the antibacterial activity by acting synergisticly.    Keywords : antibacterial, tenggulun, Staphylococcus aureus , LC-MS/MS.